Implementation of Cardiopulmonary Resuscitation in Patients with Cardiac Arrest - H. Isa, Karsum; Thalib, Abdul Herman Syah (Inspirasi Foundation, 2025)
Introduction: One of the emergency conditions that can occur anywhere and anytime, is life-threatening, and requires immediate treatment is cardiac arrest. Cardiac arrest is a clinical condition in which circulation stops suddenly, characterized by unconsciousness, respiratory arrest, and the absence of a palpable pulse in the large arteries. Objective: This case study aims to descriptively explore the implementation of Cardiopulmonary Resuscitation (CPR) in patients experiencing cardiac arrest. Method: The study was conducted at RS Bhayangkara Makassar, South Sulawesi, on June 24, 2024. Data were collected through direct observation using an observation sheet, focusing on the CPR procedure performed by the medical team. The observation included the sequence of actions, response times, and outcomes of the CPR process. Data were presented in tables and narratives, with strict confidentiality maintained by anonymizing patient information.. Results: Prior to the administration of cardiopulmonary resuscitation (CPR), patient Mr. A experienced a decrease in consciousness with a GCS score of 4, sudden respiratory arrest, and cardiac arrest. After CPR was performed, Mr. A was declared deceased, with a success rate of CPR at 0%. Conclusion: Before CPR was performed, there were signs of decreased consciousness, an absent pulse, and no breathing. After the intervention, the patient was declared deceased.